Cooperative Purchasing Organizations and Corporate Social Responsibility in Independent Coffee Shops. - Spivey, Rowan. (2017)
Abstract: Corporate Social Responsibility is an increasingly important concern for businesses in the 21st century. Small and medium-sized enterprises, however, face a number of unique barriers to instituting socially and environmentally responsible measures. This thesis addresses the hypothesis that cooperation between small businesses can reduce some of these barriers. An in-depth case study of the Independents Coffee Cooperative in Philadelphia is used to better understand the impact that cooperation can have on businesses' efforts to increase social and environmental responsibility. It finds that though cooperation can reduce some of the barriers, including financial and information barriers, it also produces additional obstacles. Several recommendations are articulated to help guide other organizations or businesses interested in forming a similar values-based cooperative.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Ann Rappaport.; Keyword: Environmental management.